Mihái Ticán Rumano, periodista y escritor-viajero - Rosca, Angela (Revista de Filología Románica, 2006)
This study is dedicated to the life and to the work of Mihail Tican Rumanian, personality little known in the literary Hispanic American ambience, which publishes in Spain his first books of trip in Castilian. Next we present an analysis books on Africa and Spain. At the same time we focus on the importance of Tican in Hispanic-Rumanian approach across his journalistic activity and the newspaper Dacia edited in Barcelona on 1929.